Analisis Kinerja Unit Pelaksana Teknis Daerah Perlindungan Perempuan Dan Anak Provinsi Bali Dalam Menangani Kasus Kekerasan Dalam Rumah Tangga Di Kota Denpasar - Paramadhyaksa, Anak Agung Ngurah Mayun; Supriliyani, Ni Wayan; Winaya, I Ketut (CITIZEN CHARTER, 2023)
The purpose of the study was to analyze the performance of the Bali Province UPTD PPA in handling cases of domestic violence in Denpasar City. Analysis of the findings using the theory of Organizational Performance Agus Dwiyanto (2006). The findings show that the productivity of the organizational performance of the Bali Province UPTD is not optimal, this can be seen from the quantity of work that there are still many constraints on limited human resources. Then the quality of work provided by the Bali Province UPTD PPA is quite good with the services provided by the officers. The quality of service related to physical evidence and public trust has not been optimal. Responsiveness relates to speed and accuracy as well as community participation and assistance. Speed and accuracy are considered good enough by the community. The responsibility of the Bali Province UPTD to the community is in the form of providing alternative solutions to the problems they complain about. Keywords: Performance, Protection of Women and Children board